PENGARUH INDEPENDENSI, KEAHLIAN PROFESIONAL DAN PENGALAMAN AUDITOR INTERNAL TERHADAP EFEKTIVITAS PENERAPAN STRUKTUR PENGENDALIAN INTERN (HOTEL KELAS MELATI DI KOTA JAMBI) - Herawaty, Netty (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
The objective of this research is to analyze the effect of the independence, expertise auditor,experience of internal auditor on efectivity of internal control at melati hotel in Jambi City.The purpose of this research are to determine whether the independence, expertise auditor,experience of internal auditor simultaneously influence and partial influence on efectivity ofinternal control at melati hotel in Jambi City. Data is collected by field with primary data.The respondent of this study are internal auditor from 47 hotels. Samples taken withpurposive sampling. Analysis using multiple linear regression analysis. The results of thisresearch show that independence, expertise auditor, experience of internal auditorsimultaneously influence and partially have not significant effect on efectivity of internalcontrol at melati hotel in Jambi City.Keywords : independence, expertise auditor, experience of internal auditor, control internal